Secondary Teacher Education in Manipur — A Field Study - Patel, Madhulika S.; Pandey, Saroj (JOURNAL OF INDIAN EDUCATION, 2014)
The quality of teacher education continues to be a matter of concern all over the country and more so in the north-eastern region which suffers from numerous problems like regional violence, geographical remoteness, lack of proper connectivity and communications with rest of the country and inadequate infrastructure facilities. The problem is further compounded due to unqualified/ under qualified teachers serving at various levels of school education. The present paper is focused on the curriculum backdrop and tries to explore the existing pre-service teacher education for secondary school teachers in the North Eastern State of Manipur along with the constraints experienced by the State in organising pre-service teacher education programme. Suitable interventions are suggested for introducing desired changes in the curriculum and implementation of teacher education programmes in the State of Manipur. The information included in the paper could be of use to the policy planners and administrators for suitable interventions.